Development of Basic Accounting and Finance Books Based on Differences Learning Style for Vocational School - Reza Ayu Palupi; Susanti Susanti; Agung Listiadi (Universitas Negeri Semarang, 2023)
This study aims to produce textbooks on Fundamentals of Accounting and Financial Institutions based on learning style differentiation as an alternative teaching material for teachers and student classes at State Vocational Schools in Surabaya, which consist of State Vocational School 1 Surabaya, State Vocational School 4 Surabaya, State Vocational School 6 Surabaya, and State Vocational School 10 Surabaya as well as knowing the effectiveness of using accounting textbooks based on learning style differentiation. The product produced in this study is a textbook on Fundamentals of Accounting and Finance adapted to the Merdeka Curriculum. This research is a research that uses mixed methods consisting of development research and experimental research. The development was carried out using the 4D development model from Thiagarajan which was carried out in full, namely definition, design, development and deployment. Data in this study were collected using questionnaires and tests and analyzed using descriptive analysis of proportions and t test (paired-samples t test). The results showed that overall the average proportion of eligibility for open books was very feasible. This shows that the developed textbook has valid criteria and is feasible to use. Based on the results of the t test (paired-samples t test) it is known that there are differences in motivation and student learning outcomes before and after being given treatment in the form of accounting textbooks based on learning style differentiation which indicates that textbooks have an effective effect.